Peningkatan Kualitas Emping Melinjo melalui Proses Pengepresan dan Penurunan Kadar Purin di UKM Emping Jago - Rizky Brisha Nuary; Rahmania Nur Afiah; Anis Asmediana; Lativa Lisya Maghfira; R. Baskara Katri Anandito (Universitas Sebelas Maret, 2023)
Quality Improvement of Emping Melinjo through Pressing Process and Reduction of Purin Level at SME Emping Jago. Emping melinjo is one of the popular foods among Indonesians. Kartasura is one of the districts in Sukoharjo that has potential in the production of emping melinjo. This study aimed to improve the quality of emping melinjo by using a mechanical pressing machine and reducing the purin level. The method used was a literature review based on scientific journals, books, and others. The results were to substitute the pressing process using mechanical machinery and by soaking treatment to reduce the purin levels. The improvement on pressing process were performed as an innovation so the process will not depend on human workers. Then, the soaking in a 4% acetic acid solution (vinegar) varied for 0; 10; 20; and 40 minutes.The hypoxanthine and adenine levels (in micrograms per gram), according to the soaking duration, showed 46,43; 41,50; 41,05; 36,71; and 124,74; 110,90; 109,83; 108,82 respectively. The 40 minutes soaking process could decrease the purin level by 20%.